Providing Variations of Learning Modalities to Scaffold Pre-Service EFL Teachers in Designing Lesson Plan - Setyono, Budi (Proceeding of International Conference on Teacher Training and Education, 2016)
The present study reported self-reflective study on Instructional Design (ID) course at an English Education Department, East Java in a period of one semester. Â In this study, I did self-reflection throughout the whole process of my teaching program applying variations of learning modalities. This self-reflection examined the problems experienced by pre-service teachers in designing lesson plan, examined impacts of implementing variations of learning modality in scaffolding the construction of group and individual lesson plan, and described response made by course participants having joined ID course. The data collection technique used to elicit problems faced by pre-service teachers in designing lesson plan were document analysis of lesson plan and conference with pre-service teachers. Field notes and diary were used to collect data about how variations of learning modalities (i.e. modelling, peer collaboration, individual task) help pre-service teachers design lesson plan. Written reflection made by pre-service teachers was used to collect data about responses towards ID course. The findings revealed that variations of learning modalities could help pre-service teachers in the process of writing effective lesson plan. Through modelling, pre-service teachers could recognize deeply about the features of lesson plan structure. Through collaboration, students could acquire both social skills (communication skill, responsibility, trust, respect, care, and tolerance) and academic skills (ability to create effective lesson plan). In independent task, pre-service teachers became more self-directed learners and gained confidence in accomplishing the task. The result of critical reflection revealed that pre-service teachers responded positively towards variations of learning modalities provided in ID course.Â Â